Long-term impact of coronavirus disease 2019 pandemic on emergency department utilization in a metropolitan emergency department in Korea - Seung Yeon Hwang; Jae Kwang Lee; Hyun Sik Ryu; Seong Soo Park; Jun Young Choi; Hye Ji Lee; Seung Ho Hur; Yeong Geun Park; Hyun Soo Choi (Pediatric Emergency Medicine Journal, 2021)
Purpose As coronavirus disease 2019 pandemic has been prolonged, it became crucial to analyze the long-term impact of the pandemic on emergency department (ED) utilization for efficient use of emergency medicine resources. Methods We reviewed the data of children (≤ 18 years) who visited the ED in Daejeon, Korea, from February 2019 through January 2021. This period was dichotomized by February 2020 into the reference and pandemic periods. The latter period was further divided into the early (February-August 2020) and late pandemic periods. Between the reference and pandemic periods, and between the early and late pandemic periods, we respectively compared proportions of children in all patients (including adults), age groups, high acuity (the Korean Triage and Acuity Scale 1-2), diagnostic codes, visits via ambulances, ED length of stay, and ED disposition. Results Compared to the reference and early pandemic periods, the pandemic and late pandemic periods respectively showed changes as follows: proportion of children in all patients (from 29.8% to 19.0% and from 19.8% to 18.1%; all Ps < 0.001), children younger than 5 years (from 56.7% to 49.9% and from 52.1% to 47.4%; all Ps < 0.001), high acuity (from 12.0% to 7.8% [P < 0.001] and from 8.8% to 6.7% [P = 0.004]), “Injury, poisoning and certain other consequences of external causes (S00-T98; from 30.0% to 49.0% and from 48.3% to 49.8%),” and “Diseases of the respiratory system (J00-J99; from 29.6% to 10.3% and from 12.8% to 7.5%).” Increases in the visits via ambulances, ED length of stay, children undergoing intensive care unit hospitalization or death were noted only in comparison between the reference and pandemic periods. Conclusion A long-term impact of the pandemic on ED use may be a decrease in the proportion of young or ill children.